1998
DOI: 10.1128/jcm.36.4.902-907.1998
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcal Vir Types Are M-Protein Gene (emm) Sequence Type Specific

Abstract: The M-protein genes (emm genes) of 103 separate impetiginous Streptococcus pyogenes isolates were sequenced and the sequence types were compared to the types obtained by Vir typing. Vir typing is based on restriction fragment length polymorphism (RFLP) analysis of a 4- to 7-kb pathogenicity island encodingemm and other virulence genes. By using bothHaeIII and HinfI to generate RFLP profiles, complete concordance between Vir type and emm sequence type was found. Comparison of the emm sequences with those in Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
1
13
2
Order By: Relevance
“…Further polymorphism within the Vir types was scored by emm typing which differentiated 16 VTs into 23 emm types indicating 57AE5% heterogeneity. Vir type-specific emm type was observed in most of the clinical isolates, which confirmed that heterogeneity is because of variation in the emm gene rather than diversity in architecture of the Vir regulon (Gardiner et al 1998). In contrast few samples from our study showed same emm type for isolates showing different VTs.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Further polymorphism within the Vir types was scored by emm typing which differentiated 16 VTs into 23 emm types indicating 57AE5% heterogeneity. Vir type-specific emm type was observed in most of the clinical isolates, which confirmed that heterogeneity is because of variation in the emm gene rather than diversity in architecture of the Vir regulon (Gardiner et al 1998). In contrast few samples from our study showed same emm type for isolates showing different VTs.…”
Section: Discussionsupporting
confidence: 78%
“…The results when analysed with the data available from other countries highlighted significant diversity within this small number of isolates screened from north India. Reports from Australia indicated 10% heterogeneity by grouping 407 isolates of GAS into 42 distinct genotypes (Cleary et al 1991) and 19% variation by showing 20 Vir types among 103 GAS isolates (Gardiner et al 1998). Similarly, another report from Romania (Surdeanu et al 2000) accounted for 34% diversity in GAS isolates by showing 22 Vir types from 64 isolates.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations